Pembentukan Identitas Kolektif pada Gerakan Konservasi Mangrove: The Collective Identity Formation of a Mangrove Conservation Movement - Akhmad Fauzie; Suryanto Suryanto; Andik Matulessy (Jurnal Psikologi Teori dan Terapan, 2021)
This study aims to understand the collective identity formation of Kelompok Pantai Lestari (KPL) as the mangrove conservation movement. This study employed a qualitative method with a constructivist grounded theory. The subjects of this study were 4 peoples who are the founders of KPL. Data were collected using in-depth interviews and analyzed through the steps from open, axial, and selective codings to the creation of a conceptual model of the collective identity formation in a mangrove conservation movement. The social representation theory was used as the framework that guided the data analysis. The results show that the foundation of the KPL as a conservation movement was related to the production of social knowledge among existing conservation groups on the importance of ecological values for improving welfare. KPL has been playing major role in producing local wisdom on environmental conservation and advocating the making of local regulations which put scientific knowledge into practice. The KPL’s mangrove conservation initiatives indicates that coastal communities have the potential to become a thinking society in environmental preservation; thus, it can be a reference for social engineering in environmental conservation that emphasizes on the collective action and identity. Keywords: Collective identity, conservation, social movement, social representation   Abstrak: Penelitian ini bertujuan untuk memahami pembentukan identitas kolektif pada Kelompok Pantai Lestari KPL) sebagai gerakan konservasi mangrove. Penelitian ini menggunakan pendekatan kualitatif dengan metode constructivist grounded theory. Subjek penelitian adalah pendiri KPL berjumlah 4 orang. Data dikumpulkan melalui wawancara mendalam dan dianalisis mengikuti tahapan pengolahan data dari pengkodean open, axial, dan selektif hingga pembuatan model konseptual pembentukan identitas kolektif gerakan konservasi mangrove. Teori representasi sosial dimanfaatkan dalam interpretasi data. Hasil analisis menunjukkan lahirnya KPL sebagai gerakan konservasi menandai cara kerja representasi sosial yang berpusat pada produksi pengetahuan sosial tentang kelembagaan kelompok konservasi dan pentingnya nilai ekologis untuk peningkatan kesejahteraan. KPL berperan besar dalam memproduksi kearifan lokal dengan mengadvokasi lahirnya peraturan daerah yang mengkonstruksi pengetahuan ilmiah menjadi pengetahuan praktis dalam kehidupan sehari-hari. Keberhasilan KPL sebagai gerakan konservasi mangrove menunjukkan bahwa masyakat pesisir memiliki potensi sebagai sebuah masyarakat berpikir, dan dapat menjadi contoh rekayasa sosial dalam gerakan konservasi yang mengandalkan pada tindakan dan identitas kolektif.